Structural and Optical Studies of 100 MeV Ni+7 Irradiated Cadmium Selenide Thin Films - Rajesh Singh; A.D. Yadav; V. Jadhav; S.K. Dubey (Журнал нано- та електронної фізики)
The effect of irradiation with Swift (100 MeV) Ni+ 7 ions on the structural and optical properties of Cadmium Selenide (CdSe) thin films have been investigated at different fluencies in the range of 1  1011-1  1013 ions/cm – 2. The CdSe films on glass substrates were prepared by thermal evaporation. The structural and optical changes with respect to increasing fluence were observed by the means of X-ray diffraction (XRD), UV-VIS and Raman spectroscopy. After irradiating the films with Ni+ 7 ions XRD show the increased in peak intensity and crystallite size with increasing fluence. The UV-VIS-IR spectroscopy revealed that there is decrease in band gap energy of the films after irradiation with increasing fluencies. Raman spectrum for as deposited and irradiated films show two peak, one at 209 cm – 1 and at 410 cm – 1 which is assigned to the longitudinal optical (LO) phonon mode.